1997
DOI: 10.1159/000244402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fetal Nephrectomy on Insulin-Like Growth Factors and Their Binding Proteins in Sheep

Abstract: Bilateral nephrectomy retards fetal growth and decreases somatomedin (insulin-like growth factor-I, IGF-I) activity. To determine whether nephrectomy alters the synthesis of IGF-I or its binding proteins (IGFBPs), we studied 6 sets of twin fetuses. Kidneys were removed bilaterally from 1 twin of each set at 112–122 days of gestation (term 145 days). Plasma IGF-I concentrations were greater in nephrectomized fetuses than in the intact twins during the 1st week (261 ± 35 vs. 153 ± 21 ng/ml, p < 0.02; mean ± SE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The finding that the two groups of foetuses were similar in weight was in agreement with other studies in which foetuses have been nephrectomized late in gestation. 3,5,8,18 In the second part of this study, our aim was to determine which of the changes observed following nephrectomy could be attributed to absence of the foetal RAS. Therefore, the dose of AngII used for the continuous infusion (1.5 g/kg per h) was chosen to provide replacement levels of AngII.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding that the two groups of foetuses were similar in weight was in agreement with other studies in which foetuses have been nephrectomized late in gestation. 3,5,8,18 In the second part of this study, our aim was to determine which of the changes observed following nephrectomy could be attributed to absence of the foetal RAS. Therefore, the dose of AngII used for the continuous infusion (1.5 g/kg per h) was chosen to provide replacement levels of AngII.…”
Section: Discussionmentioning
confidence: 99%
“…Many workers have reported at least one of these blood gas changes after foetal nephrectomy. 5,6,8,18 The poorer blood gas status after nephrectomy may have been due to several factors. First, the nephrectomized foetuses had lower HR and, therefore, possibly lower cardiac outputs and reduced placental blood flows compared with intact foetuses.…”
Section: Arterial Blood Gasesmentioning
confidence: 99%
See 1 more Smart Citation